2017
DOI: 10.1088/1674-1056/26/1/018103
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoelectric effect in multiferroic NdMn 2 O 5

Abstract: We have measured the dielectric constant for NdMn 2 O 5 in an external magnetic field to map out the magnetoelectric phase diagram. The phase diagram corresponds well with the previously reported data of neutron diffraction and magnetic susceptibility. Our main finding is the observation of a dielectric anomaly in the low temperature phase with a strong magnetoelectric effect, which is attributed to the independent Nd 3+ ordering. Moreover, the absence of the dielectric anomaly in the paramagnetic phase is dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Tesla, exactly in the ICM2/FE phase. Coinciding with the transition observed in the magnetization measurements in Fig 3(d), this variation could be related to a magnetic-fieldinduced transition CM+ICM2/FE → ICM2/FE [18,43] as a consequence of a renormalization of the KD g tensors. This renormalization increases with the level energy and could be helpful for the CF parameters modeling.…”
Section: Broadenings Of the Cf Excitations Are Similar To What We Hav...supporting
confidence: 63%
“…Tesla, exactly in the ICM2/FE phase. Coinciding with the transition observed in the magnetization measurements in Fig 3(d), this variation could be related to a magnetic-fieldinduced transition CM+ICM2/FE → ICM2/FE [18,43] as a consequence of a renormalization of the KD g tensors. This renormalization increases with the level energy and could be helpful for the CF parameters modeling.…”
Section: Broadenings Of the Cf Excitations Are Similar To What We Hav...supporting
confidence: 63%
“…These multiferroic compounds show variety of phase transitions in the low temperature range (2-45 K) along with strong magnetoelectric coupling. Previously, we have also investigated the low temperature phase transition in NdMn 2 O 5 , GdMn 2 O 5 , and DyMn 2 O 5 [8][9][10]. Remarkably, we have observed a new magnetic correlation in the dielectric response at slightly higher temperature above Néel temperature (T N ) [8,9].…”
Section: Introductionmentioning
confidence: 77%
“…The similarity in magnetic structure of RMn 2 O 5 would imply the similarity of electric polarization in response to these magnetic ordering sequences in the low-T range. However, measured data from several systems [26][27][28][29] or even from the same system but different samples synthesized by different authors did show big scattering [18,[30][31][32] as shown in Fig. S1 of Supplementary Material.…”
Section: Introductionmentioning
confidence: 96%